Prospective study of sound localization patents componentes of the assessment the central auditory processing (Research, Society and Development, 2021)
Objective: A technological survey was carried out, with the objective of obtaining information about the existence of equipament, with assesses the sound location during the Central Auditory Processing Test. Methodology: The search was carried out using the INPI, Espacenet, Patentscope e Patentinspiration databases. The terms “localization”, “sound”, “auditive” and “loudness perception” were used, interconnected by boolean operators “AND” e “OR”, to form various algorithms. The research was carried out in the title and summart Fields, using terms in Portuguese in national patentes and English in international patents. In veiw of the recorvered patentes. Result and Discussion: In view of the recorvered, 3 were considered to be close to the research topic. However, only of them served to guide the parameters of the patente under study. Conclusion: However, none refers to the use of equipament in order to assess the ability of localization during the assessment of the Central Auditory Processing. This indicates the novelty of the proposed theme.